2018
DOI: 10.1016/j.jclinepi.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Registered trials report less beneficial treatment effects than unregistered ones: a meta-epidemiological study in orthodontics

Abstract: Signs of bias from lack of trial protocol registration were found with nonregistered trials reporting more beneficial intervention effects than registered ones. Caution is warranted by the interpretation of nonregistered randomized trials or systematic reviews thereof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Results showed that 57% of the studies published before 2000 showed a significant benefit of the intervention, as opposed to only 8% of trials published after 2000. Similar results were 9 reported in a (preregistered) meta-analysis of meta-analyses of orthodontics and dentofacial orthopedics studies: registered trials reported less favorable intervention effects compared to unregistered trials (Papageorgiou et al, 2018) . Preregistration can also help identify whether funding sources are correlated with study outcome, potentially uncovering questionable practices due to (undisclosed) conflicts of interest.…”
Section: Advantages Of Preregistrationsupporting
confidence: 85%
“…Results showed that 57% of the studies published before 2000 showed a significant benefit of the intervention, as opposed to only 8% of trials published after 2000. Similar results were 9 reported in a (preregistered) meta-analysis of meta-analyses of orthodontics and dentofacial orthopedics studies: registered trials reported less favorable intervention effects compared to unregistered trials (Papageorgiou et al, 2018) . Preregistration can also help identify whether funding sources are correlated with study outcome, potentially uncovering questionable practices due to (undisclosed) conflicts of interest.…”
Section: Advantages Of Preregistrationsupporting
confidence: 85%
“…It is worth mentioning that only two of the studies under consideration in the systematic review reported being registered trials, none of which could be included in the meta-analysis. Several meta-research studies show that effect sizes tend to be substantially smaller in registered trials (Kaplan and Irvin 2015;Papageorgiou et al 2018), possibly due to selective reporting and other biases in unregistered research that artificially inflate effect sizes (Kerr 1998;Simmons et al 2011). Ideally, future RCTs conducted in this topic should adhere to preregistered protocols and analysis plans, to ensure that their results are free from these sources of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that direction of primary outcomes, i.e., statistically significant or not, doesn’t seem to be related with the registration status. Previous studies evaluating association between trial registration and treatment effect size have reported inconsistent results [21,46] and another recent study reported that direction of primary outcome was not subject to the status of registration [47]. Given these inconsistent results, a larger meta-epidemiological and/or cross-sectional study encompassing various medical disciplines is needed to determine the association between trial registration and treatment effect size and/or direction of study outcomes.…”
Section: Discussionmentioning
confidence: 99%